2014
DOI: 10.1186/1471-2393-14-46
|View full text |Cite
|
Sign up to set email alerts
|

Caseload midwifery compared to standard or private obstetric care for first time mothers in a public teaching hospital in Australia: a cross sectional study of cost and birth outcomes

Abstract: BackgroundIn many countries midwives act as the main providers of care for women throughout pregnancy, labour and birth. In our large public teaching hospital in Australia we restructured the way midwifery care is offered and introduced caseload midwifery for one third of women booked at the hospital. We then compared the costs and birth outcomes associated with caseload midwifery compared to the two existing models of care, standard hospital care and private obstetric care.MethodsWe undertook a cross sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 21 publications
2
49
0
1
Order By: Relevance
“…In this study, a “standard primipara”, defined as a first time, “low‐risk” mother, was used as the unit of comparison, to reduce differences between the caseload care, standard hospital care and private obstetric care groups. Women who received caseload care were more likely to have a spontaneous onset of labour and an unassisted vaginal birth and less likely to have an elective caesarean delivery than those in the other two groups, with lower average costs of care 24 …”
Section: Midwifery Continuity Of Care Models: the Evidence For Benefitmentioning
confidence: 71%
See 1 more Smart Citation
“…In this study, a “standard primipara”, defined as a first time, “low‐risk” mother, was used as the unit of comparison, to reduce differences between the caseload care, standard hospital care and private obstetric care groups. Women who received caseload care were more likely to have a spontaneous onset of labour and an unassisted vaginal birth and less likely to have an elective caesarean delivery than those in the other two groups, with lower average costs of care 24 …”
Section: Midwifery Continuity Of Care Models: the Evidence For Benefitmentioning
confidence: 71%
“…Midwifery continuity of carer has also been examined in non‐randomised studies, although these carry an inherently increased risk of bias. These include a study in a large referral centre in Sydney, where a third of pregnant women received care through a midwifery continuity of care (caseload care) model 24 . Midwives were organised in groups of four and were responsible for the care of a specified caseload of women throughout pregnancy, birth and the post partum period 25 .…”
Section: Midwifery Continuity Of Care Models: the Evidence For Benefitmentioning
confidence: 97%
“…Our results indicate that perhaps more small midwife-led units would allow for low-risk women to receive better care, especially during early labour. Two large studies from Australia have shown that case-load midwifery, that is, having a known midwife during antenatal, intrapartum and postpartum care, increased the likelihood of later admission in a later stage of labour [43] and for primiparas an increased proportion of spontaneous onset of labour, reduction in caesarean sections and lower costs [44].…”
Section: Article In Pressmentioning
confidence: 99%
“…Case‐load midwifery describes a continuity of care model in which women see one midwife or a partner midwife for antepartum, intrapartum, and postpartum care. This model of care is also associated with higher rates of spontaneous labor, lower elective cesarean birth rates, and higher levels of maternal satisfaction with the birth experience . It would be interesting to consider research about how midwifery education can include or does include the concept of being “with woman” and the impact of this competency training on practice after education and population‐wide childbirth outcomes.…”
Section: A Contemporary Interpretation Of the Midwifery Construct Of mentioning
confidence: 99%